Literature Review: Implementasi Strategi Penanggulangan Bencana Banjir oleh Pemerintah Kota Palembang di Kecamatan Seberang Ulu I Dan Seberang Ulu II - Muhammad Aldy Irwansyah; Novrikasari Novrikasari; Mohammad Zulkarnain (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to comprehensively examine the implementation of flood disaster management strategies by the Palembang City Government, particularly in the Seberang Ulu I and Seberang Ulu II districts, through a literature review approach. These areas are highly vulnerable to flooding due to their lowland topography and proximity to the Musi River. The study employs a review of various literature sources, including scholarly journals, government policy reports, and disaster management planning documents published between 2015 and 2024. The findings reveal that the implemented flood management strategies encompass three main stages: pre-disaster, emergency response, and post-disaster recovery. At the pre-disaster stage, the Palembang City Government focuses on enhancing community capacity through disaster education and the development of drainage infrastructure. However, the effectiveness of these strategies is still hindered by several challenges, such as limited budgets, lack of inter-agency coordination, and low community participation in mitigation programs. During the emergency response phase, the government’s reaction is considered relatively quick but has yet to be fully integrated with provincial-level disaster management agencies. This review concludes that flood disaster management efforts in Palembang require stronger policies emphasizing both structural and non-structural mitigation, cross-sectoral synergy, and increased